Total protein of whole saliva as a biomarker of anaerobic threshold - Bortolini, M. J. S.; de Agostini, G. G.; Reis, I. T.; Lamounier, R. P. M. S.; Blumberg, J. B.; Espindola, F. S. (Research Quarterly for Exercise and Sport, 2009)
Saliva provides a convenient and noninvasive matrix for assessing specific physiological parameters, including some biomarkers of exercise. We investigated whether the total protein concentration of whole saliva (TPWS) would reflect the anaerobic threshold during an incremental exercise test. After a warm-up period, 13 nonsmoking men performed a maximum incremental exercise on a cycle ergometer. Blood and stimulated saliva were collected during the test. The TPWS anaerobic threshold (PAT) was determined using the Dmax method. The PAT was correlated with the blood lactate anaerobic threshold (AT; r = .93, p < .05). No significant difference (p = .16) was observed between PAT and AT. Thus, TPWS provides a convenient and noninvasive matrix for determining the anaerobic threshold during incremental exercise tests.